The Challenges of Adopting a Learner-Centered Approach to On-Line English Teacher Education: A Teacher-Research Study on Jigsaw Reading and PeerTeaching in Cambodia - Meyly Kheng; Jonathan Newton (Debrecen University Press, 2023)
In Cambodia, the shift to on-line learning due to Covid-19 reinforced an already overly teacher-centric approach to education, leading to the risk of greater learner disengagement. To address this problem, I3 embarked on a research project involving the redesign of the on-line delivery of a final year English teacher education course on 'School and Society', in which all lectures were replaced with jigsaw reading (JR) and peer teaching (PT) tasks. To track the impact of this innovation, I recorded class sessions, kept observation logs, and obtained data from students' reflective journaling, interviews, and a focus group. This paper reports on the design principles behind the innovation and its impact on student motivation and engagement. The research has implications for on-line teacher education and the introduction of learner-centered pedagogies in global south contexts.